Studies on western Pacific gorgonians (Anthozoa: Octocorallia). Part 3: towards a revision of the bamboo corals (Keratoisididae) with descriptions of three new genera and four new species - Xu, Yu; Lu, Bo; Watling, Les; Zhan, Zifeng; Wang, Chunsheng; Xu, Kuidong (Zootaxa, 2024)
Members of clade J3 in Keratoisididae form a large monophyletic branch but show a diversity of morphological features. Based on an integrated taxonomy approach, six specimens of deep-sea bamboo corals (Octocorallia: Keratoisididae) collected from the seamounts in the Western Pacific Ocean are described as three new genera and four new species of clade J3. Aethisis turriformis gen. et sp. nov. is characterized by branches originating in different planes forming a tree-shaped colony, a bare sclerite-free area present at the base of each tentacle, and in polyps and coenenchyme flat rods and thick scales often with toothed lateral edges and two rounded ends. Parajasonisis flabellata gen. et sp. nov. is characterized by alternately and biserially arranged polyps, flat rods/needles in the upper polyp body wall, and flat rods and elongate and thick scales in the basal polyp body wall and coenenchyme. Dentatisis gen. nov. is characterized by flat rods in tentacles with dentate lateral edges and two rounded and slightly expanded ends, irregular rods with conical projections in the pharynx, granulated needles and flat rods both present in polyp body wall. Dentatisis bathyalis sp. nov. has dense scales with a medial constriction in basal polyp body wall and coenenchyme, and needles forming longitudinal bands at the mesenterial insertions, extending to the upper polyp body wall. Dentatisis projecta sp. nov. is characterized by trumpet-shaped polyps with large needles projecting beyond the tentacles bases, abundant granulated rods/needles, and scales absent in polyp body wall and coenenchyme. The species in clade J3, especially the genus Dentatisis gen. nov., show high morphological differentiation. Phylogenetic analyses of mtMutS and 28S rDNA both supported the assignment of the new genera and species. Compared with mtMutS, 28S rDNA showed high genetic variation with the three new genera each forming single clades respectively with moderate to high support in 28S rDNA trees. The nuclear marker 28S rDNA may be more effective than the mitochondrial marker mtMutS, and could be a promising marker to distinguishing keratoisidid congeners.